POLITIK PENDIDIKAN DAN KONSEP KEBIJAKAN PENDIDIKAN DALAM SISTEM PENDIDIKAN INDONESIA - Raudoh; Atiah Almubarokah; Fina Amalia; Hasanda Putra, Fio; Isma Yuliza; Najma Dianah Akmalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a strategic instrument for improving the quality of human resources and an inseparable part of public policy. In practice, educational implementation is influenced by political dynamics that determine the direction, objectives, and educational policies adopted by the government. Therefore, understanding educational politics and educational policy concepts is essential for analyzing the development of Indonesia’s educational system. This study aims to describe the concept of educational politics, the scope of educational politics, educational policy, and the policy-making process within the national education system. This research employed a qualitative approach using the library research method. Data were collected from books, scientific journals, government regulations, and other relevant literature. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that educational politics refers to the government’s process of determining educational direction through policies based on national ideology, community needs, and national development goals. The scope of educational politics includes policy formulation, educational management, educational financing, equal access to education, quality improvement, and policy evaluation. Educational policy is also an integral part of public policy that undergoes stages of problem identification, policy formulation, implementation, evaluation, and policy termination. Therefore, the success of the national education system is highly dependent on educational policies that are participatory, adaptive, and oriented toward improving educational quality.